Alcea rosea root extract as a preventive and curative agent in ethylene glycol-induced urolithiasis in rats - Ahmadi, Marzieh (Medknow Publications & Media Pvt Ltd, 2012)
INTRODUCTION: Alcea rosea L. is used in Asian folk medicine as a remedy for a wide range of ailments. The aim of the present study was to investigate the effect of hydroalcoholic extract of Alcea rosea roots on ethylene glycol-induced kidney calculi in rats. MATERIALS AND METHODS: Male Wistar rats were randomly divided into control, ethylene glycol (EG), curative and preventive groups. Control group received tap drinking water for 28 days. Ethylene glycol (EG), curative and preventive groups received 1% ethylene glycol for induction of calcium oxalate (CaOx) calculus formation; preventive and curative subjects also received the hydroalcoholic extract of Alcea rosea roots in drinking water at dose of 170 mg/kg, since day 0 or day 14, respectively. Urinary oxalate concentration was measured by spectrophotometer on days 0, 14 and 28. On day 28, the kidneys were removed and examined histopathologically under light microscopy for counting the calcium oxalate deposits in 50 microscopic fields. RESULTS: In both preventive and curative protocols, treatment of rats with hydroalcoholic extract of Alcea rosea roots significantly reduced the number of kidney calcium oxalate deposits compared to ethylene glycol group. Administration of Alcea rosea extract also reduced the elevated urinary oxalate due to ethylene glycol. CONCLUSION: Alcea rosea showed a beneficial effect in preventing and eliminating calcium oxalate deposition in the rat kidney. This effect is possibly due to diuretic and anti-inflammatory effects or presence of mucilaginous polysaccharides in the plant. It may also be related to lowering of urinary concentration of stone-forming constituents.